PERSEPSI NASABAH TERHADAP PELAYANAN FRONTLINER (STUDI KASUS PADA BPR TLM) - Eldalivia Y Sooai; Paulina Y Amtiran; Rolland E Fanggidae (JAF (Journal of Accounting and Finance), 2019)
The objective of the study about “Persepsi Nasabah Terhadap Pelayanan Frontliner (Studi Kasus Pada BPR TLM)” is to determine the effect of custumer perceptions based on attitude, motivation, and past experience on frontline service in BPR TLM. This study is using quantitative descriptive approach. This study is using primary data in the form of questionnaire distributed to 100 customers who made transaction at BPR TLM and also using accidental sampling method. The result of the questionnaire regarding frontliner services wer anayzed by multiple linear regression. The result shows that customer perceptions based on attitude, motivation and past experience have significant possitive effect on frontliner services on BPR TLM. This is caused fronliner services is in line with customer’s expectations, which is shown by officer fronliner attitude who are friendly and can serve customer’s needs well. The comfort waitng room and fashion style of the officer make the customers feel that frontliner services in BPR TLM is good.